Inter-task transfer of force gains is facilitated by motor imagery - Piveteau, Eric; Di Rienzo, Franck; Bolliet, Olivier; Guillot, Aymeric (Frontiers in Neuroscience, 2023)
There is compelling evidence that motor imagery (MI) contributes to improve muscle strength. While strong effects have been observed for finger muscles, only few experiments with moderate benefits were conducted within ecological applied settings targeting large upper or lower limb muscles. The aim of the present study was therefore to extend the investigation of embedded MI practice designed to improve maximal voluntary strength on a multi-joint dynamic exercise involving the lower limbs. Additionally, we tested whether targeting the content of MI on another movement than that physically performed and involving differently the same body parts, might promote inter-task transfer of strength gains. A total of 75 participants were randomly assigned into three groups who underwent a physical training on back squat. During inter-trial recovery periods, a first MI group (n=25) mentally rehearsed the back squat, while a second MI group (n=25) performed MI of a different movement involving the lower limbs (deadlift). Participants from the control group (n=25) completed a neutral cognitive task during equivalent time. Strength and power gains were assessed ecologically using a velocity transducer device at 4 different time periods. Data first revealed that participants who engaged in MI of the back squat improved their back squat performance (p<0.03 and p<0.01, respectively), more than the control group (p<0.05), hence supporting the positive effects of MI on strength. Data further supported the inter-task transfer of strength gains when MI targeted a movement that was not physically trained (p=0.05). These findings provide experimental support for the use of MI during physical training sessions to improve and transfer force development.